( | 3 | x | − | 1 | ) | ( | 2 | x | + | 1 | ) | = | 6 | x |
Left side of the equation = | 3 | x | ( | 2 | x | + | 1 | ) | − | 1 | ( | 2 | x | + | 1 | ) |
= | 3 | x | × | 2 | x | + | 3 | x | × | 1 | − | 1 | ( | 2 | x | + | 1 | ) |
= | 6 | x | x | + | 3 | x | − | 1 | ( | 2 | x | + | 1 | ) |
= | 6 | x | x | + | 3 | x | − | 1 | × | 2 | x | − | 1 | × | 1 |
= | 6 | x | x | + | 3 | x | − | 2 | x | − | 1 |
= | 6 | x | x | + | 1 | x | − | 1 |
6 | x | x | + | 1 | x | − | 1 | = | 6 | x |
x1= | - | 1 6 |
x2=1 |